Storing cassava - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1986)
For a mere four or five cents per kilo, the storage life of cassava can be increased from a few days to two weeks, according to 'Caribbean Farm News'. This new treatment could change consumers' attitudes to cassava and make money for farmers....